Nowożytne próby rehabilitacji żony Sokratesa u Christopha Martina Wielanda, Eduarda Zellera oraz w Obronie Ksantypy Stefana Pawlickiego i Obronie Ksantypy Ludwika Hieronima Morstina - Marchewka, Anna (Collectanea Philologica, 2023)
The aim of the article is to explain how views on Xanthippe as a wife and Socrates as a husband were veriﬁed in modern times, i.e., how the defence of a woman considered the most unbearable in ancient Greece looked like. Four texts served as the most representative examples: Ch.M. Wieland’s short essay on Xanthippe, E. Zeller’s essay entitled Zur Ehrenrettung der Xanthippe and S. Pawlicki’s the ﬁctitious defence speech of Ksantypa (titled The Apology Xanthippe), and L.H. Morstin’s comedy The Apology Xanthippe. It should be emphasized that the above-mentioned writers and researchers of antiquity were clearly inﬂuenced by their predecessor.